2015
DOI: 10.1021/jf504761m
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Some Essential Oils on Phagocytosis and Complement System Activity

Abstract: The aim of the present study was to investigate the in vitro activity of 15 essential oils, 4 essential oil fractions, and 3 pure compounds (thymol, carvacrol, and eugenol) on phagocytosis by human neutrophils and on complement system. Samples were characterized by GC and GC-MS. Most of the oils (nutmeg, clove, niaouli, tea tree, bay laurel, lemon, red thyme, ginger), nutmeg terpenes, eugenol, and carvacrol showed mild to moderate inhibition of phagocytosis (25-40% inhibition at doses ranging from 40 to 60 μg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
(69 reference statements)
0
28
0
Order By: Relevance
“…The results showed that antibacterial activity of EOL and tea tree oil was much higher than that of other essential oils. A large number of studies have shown that tea tree oil has antibacterial activity (Pérez‐Rosés, Risco, Vila, Peñalver, & Cañigueral, ), but little is known on the antibacterial activity of EOL.…”
Section: Resultsmentioning
confidence: 99%
“…The results showed that antibacterial activity of EOL and tea tree oil was much higher than that of other essential oils. A large number of studies have shown that tea tree oil has antibacterial activity (Pérez‐Rosés, Risco, Vila, Peñalver, & Cañigueral, ), but little is known on the antibacterial activity of EOL.…”
Section: Resultsmentioning
confidence: 99%
“…11,3234 Furthermore, essential oils from various plants, including Artemisia spp., have been reported to exhibit various biological effects in vitro and in vivo . 2,35 In the present study, we defined the chemical profile of essential oils isolated from A. kotuchovii and evaluated their effects on phagocyte function.…”
Section: Discussionmentioning
confidence: 99%
“…1 For example, pharmacological evaluation of tarragon extracts demonstrated anti-inflammatory activity. 1,10 Although tarragon essential oil was inactive in modulating human neutrophil phagocytosis, 11 essential oils from other Artemisia spp. exhibited some immunomodulatory properties, such as inhibition of nuclear factor (NF)-κB transcriptional activity and stimulation of nitric oxide and prostaglandin E 2 production by macrophages.…”
Section: Introductionmentioning
confidence: 99%
“…Other health benefits of thymol are shown in Table 5, including anticarcinogenesis (Deb et al, 2011;Nikolić et al, 2014) and analgesic activities in vitro (Wagner & Wierer, 1986), as well as the modulation of the immune system in vitro and in vivo (Al-Kassie, 2009;Pérez-Rosés et al, 2015) by several mechanisms. Moreover, several researchers have revealed that thymol (alone or in combination with other herbal constituents) may improve animal (e.g., chickens) growth and performance in vivo together with other benefits (Al-Kassie, 2009; Hashemipour et al, 2013), but it seems to depend on the experimental conditions tested (Haselmeyer et al, 2015; Table 6).…”
Section: Othersmentioning
confidence: 99%